Review: Potensi Pengembangan Membran Polimer Hidrofilik untuk Produksi Biodiesel Berbasis Mikroalga - Widi Citra Lestari; Ellyzia Sukma Ningtiar; Mochammad Yusuf Irianto; Nurul Widiastuti (LPPM ITK, 2021)
Harvesting microalgae is an important process to be carried out in the production of biodiesel from microalgae. The method of harvesting by filtration technique provides many advantages over other methods. Polymer is a membrane material that is often used for harvesting microalgae. However, polymer membranes have limited hydrophobic properties, thus, modification was needed to improve the hydrophilic properties and performance of polymer membranes. The polyvylene fluoride (PVDF) flat-sheet membrane has advantages over other membrane materials which are rated with a flux rate of 67.3 L / m2h and a rejection value of 100%. Then, the development with hollow fiber modulation on the PVDF membrane was considered very suitable, which was reported to have succeeded in increasing the membrane flux in the harvest of Scenedemus Acuminatus reaching up to 5136 L / m2h. The addition of PVDF with the inorganic additive LiCl was successful in increasing its hydrophilicity as the water permeation size increased up to 542 L / m2h. In addition, the use of triethyl phosphate (TEP) as a solvent is more environmentally friendly and compatible with PVDF membranes. As a result, it can increase membrane porosity by up to 92.7%. Apart from improving the membrane material, this review also reports the design and economic analysis to produce an effective and efficient of polymeric membranes for microalgae harvesting.